Scholasticism reformed : essays in honour of Willem J. van Asselt - Wisse, Maarten, 1973-; Sarot, Marcel.; Otten, Willemien.; Asselt, W. J. van. (Studies in Theology and Religion, 2010)
This Festschrift celebrates Professor Willem J. van Asselt's many contributions to the study of Reformed scholasticism on the occasion of his retirement from Utrecht University. The authors argue that the resurgence of interest in scholasticism, especially in Reformed scholasticism, has in turn reformed our views of scholasticism. While most of the volume's essays contribute to the reassessment of scholasticism through relevant historical case studies or new systematic analyses of the value and validity of scholasticism for contemporary theology, some authors endeavour a critical confrontation with various aspects of this reassessment. Thus, this volume not only mirrors Van Asselt's interest in the sound historical evaluation of Reformed scholasticism and its application to contemporary philosophical theology, but also provides cutting-edge scholarship on a major development in historical theology.